SBA-15 for Effective Removal of Mercury(II) from Aqueous Solution - Zhai, Qing-Zhou; Ma, Yu-Qin; Yu, Hui; Liu, Xu-Hong (Asian Journal of Chemistry, 2011)
Because of its good structural function, excellent hydrothermal stability, steady framework structure, easily modified interior surface and certain wall thickness with easily blended element, SBA-15 has a bright applied foreground in various domains, such as adsorption-separation, environment, catalysis and light, electricity, magnetism, etc. Molecular sieve SBA-15 was prepared by hydrothermal method in this paper. By means of X-ray diffraction and scanning electron microscopy, the products were characterized. The modified SBA-15 were prepared by surface modification method with mercaptoethanol and thioglycollic acid. The pre-modified and postmodified materials were used as sorbents to evaluate the effects of acidity, temperature and time on the adsorption of Hg2+. The adsorptive experimental results showed that the optimum adsorbent was the SBA-15 obtained by the modification of thiolycollic acid. The optimal adsorptive conditions were: pH = 5, temp. 20 ºC and the adsorptive time was 50 min. The experimental results indicated that the best desorbent was 0.1 mol/L HCl. The highest rate of desorption of 75.05 % could be reached at the desorption of 2 h.